MOTIVASI INTRINSIK SEBAGAI VARIABEL INTERVENING UNTUK PELATIHAN DAN KOMPETENSI TERHADAP PENGEMBANGAN KARIR - Rossalina Dyah Rizky Hardianti; Indarto Indarto; Adijati Utaminingsih (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to analyze the influence of training and competency on career development of KPP Pratama Semarang Barat employees with intrinsic motivation as an intervening variable. The sample in this study amounted to 116 respondents using the saturated sampling method or census research method. The data collection method used is the questionnaire method and data analysis method using SmartPLS software. The test results show that only competence has a positive and significant effect on intrinsic motivation. Apart from that, the variables of training, intrinsic motivation and competence which are mediated by intrinsic motivation are also able to have a significant influence on the career development of KPP Pratama Semarang Barat employees. Meanwhile, the competency and training variables mediated by intrinsic motivation have no significant effect. This research aims to analyze the influence of training and competency on career development of KPP Pratama Semarang Barat employees with intrinsic motivation as an intervening variable. The sample in this study amounted to 116 respondents using the saturated sampling method or census research method. The data collection method used is the questionnaire method and data analysis method using SmartPLS software. The test results show that only competence has a positive and significant effect on intrinsic motivation. Apart from that, the variables of training, intrinsic motivation and competence which are mediated by intrinsic motivation are also able to have a significant influence on the career development of KPP Pratama Semarang Barat employees. Meanwhile, the competency and training variables mediated by intrinsic motivation have no significant effect.